D’un monde à l’autre ou les rhétoriques de l’exemple dans les manuels de microéconomie - Sophie Jallais (Revue de la Régulation)
In France, for more than 15 years, many economics students have urged their professors to leave “imaginary worlds” behind. This paper takes this plea as an invitation to interrogate ourselves about the world(s) we tell our students about. In this context, it proposes a typology of the worlds outlined in the examples we find in microeconomics textbooks. Four types are distinguished: real, abstract, imaginary and impossible worlds. We then show that these impossible worlds cause pedagogical problems, not only due to theirs characteristics, but also because of the discourses in which they take place. These problems cannot be solved without a serious discussion about scope and method of microeconomics.